GESTÃO DOS RESÍDUOS DO SETOR INDUSTRIAL SUCROENERGÉTICO: ESTUDO DE CASO DE UMA USINA NO MUNICÍPIO DE RIO BRILHANTE, MATO GROSSO DO SUL - Nogueira, Maria Aparecida Farias de Souza; Garcia, Marli da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The sugarcane industry has provided socio-economic development in the regions where they are deployed sugar mills and alcohol to generate direct and indirect jobs, is the fact that income generator. There must be monitoring of activities within the production process with the implementation of a SWMP (Plan Solid Waste Management), so that development does not bring high cost to the environment and consequently the health and welfare of population. The survey was conducted as a case study of waste management at a plant in Mato Grosso do Sul, through exploratory research, technical visits and questionnaire. On waste management and sustainability practices to reduce environmental impacts, the survey revealed some important points: agribusiness study adopts the policy of reuse of waste generated for the sustainable development of its activities.